Citizen participation, local government and NGOs:An experience of grassroots leadership in Nicaragua - Figueroa, María de los Dolores (Bilwi :URACCAN, 2001)
The purpose of this MRP is to analyse citizen participation in the context of infra-structural programs and actions of urban improvement encouraged by local government, churches, and nongovernmental organisations in Bluefields, RAAS, Nicaragua.
Incluye Índice
Col. Tesis
Keywords: 1. ORGANIZATION OF THE ATLANTIC